Motivasi Kerja Terhadap Hasil TBS Pada Kebun Inti 2 PT Pinago Utama Kabupaten Musi Banyuasin Provinsi Sumatera Selatan - Christian Yosua Salomo Aritonang (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to determine the role of work motivation on the results of TBS PT Pinago Utama Musi Banyuasin district of South Sumatra province. Secondly to know the constraints and problems on the results of TBS employees in PT Pinago Utama Musi Banyuasin district of South Sumatra province. This research was conducted at PT Pinago Utama Kebun Inti 2 regency of Musi Banyuasin, South Sumatera Province which lasted for 1 (one) month from 1 December 2023 until January 10, 2024. The research method used is descriptive method. Research respondents were 66 people harvesting employees, 10 people harvesting mandates, 6 person division assistants calculated using Slovin formula. For a total of 82 people selected based on the technique by taking a selective person or object of research and have specific characteristics (purposive sampling). The instruments used are job satisfaction, work morale, reward, sanction, education, salary, and FFB result. Data analysis using cobb douglass regression analysis technique. The results of this study found that: first there was no significant effect of job satisfaction on FFB results. Second there is a significant influence of morale on the FFB result. The three significant effects of rewarding FFB outcomes. The four significant effects of sanctions on FFB outcomes. the five significant educational influences on TBS outcomes. The six significant effects of salary on FFB outcomes. Thus, job satisfaction is insignificant due to heavy workloads using BJR's system (average weighted weight) with fixed tonnage basis, but morale, reward, sanction, education, significant salary as firms pay attention to awarding in the form of rice and cooking oil and the appropriate salary UMR Musi Banyusian area.